Rationality of Antibiotic use in Patients with Urinary Tract Infections at the Dr Oen Kandang Sapi Hospital Inpatient - Anggraini, Truly Dian; Ariyani, Rista (GLOBAL HEALTH SCIENCE GROUP, 2023)
Urinary tract infection is an infectious disease that requires antibiotics in its treatment. In Indonesia, UTI cases reach 180,000 cases per year. The aim of the research is to determine the pattern of antibiotic use and the appropriateness of antibiotic use in UTI patients at Dr Oen Kandang Sapi Hospital in 2021. The method used is non-experimental by collecting data retrospectively from medical records of patients diagnosed with UTI in 2021, then the data is analyzed using the method Gyssens. and analyzed quantitatively descriptively. The results of this study were an analysis of the accuracy of antibiotics using the Gyssens method in UTI patients at DR Oen Kandang Sapi Hospital, with 45 rational prescriptions (54.88%) and 37 irrational prescriptions (45.12%). Inaccuracy in the IVA category was 2 prescriptions, IVC was 8 prescriptions, in category IIIA was 1 prescription, in category IIIB was 3 prescriptions, category IVA, IVC was 8 prescriptions, category IVC, IIIB was 5 prescriptions, category IVA, IVC, IIIB was 9 recipes, category IIA, IIB 1 recipe, category IVA, IVC, IIB 1 recipe. The conclusion of this study is that the most widely used UTI antibiotic is a single type of antibiotic with 67 prescriptions (81.71%), the most widely used class of antibiotic is the cephalosporin class of antibiotics with 60 prescriptions (61.22%), the most common type of antibiotic. The antibiotic ceftriaxone used was 42 prescriptions (42.42%).